CULTURAL DIFFERENCES IN ENGLISH LANGUAGE LEARNING - Behruzkhon Yuldoshev Behzod ugli (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This article examines how cultural differences influence English language learning across diverse contexts, with special attention to non-native environments such as Central Asia. It explores the ways cultural norms, communication styles, and learning traditions shape students’ attitudes, motivation, and classroom behavior. The discussion highlights that understanding and respecting cultural diversity in English teaching enhances intercultural competence, communicative effectiveness, and learner engagement.